Challenge in Early Diagnosis of Rare Lymphomas – A Case of Monomorphic Epitheliotropic Intestinal T-cell Lymphoma Masquerading as Enteritis. (28th October 2021) - Qiu, W; Khokhar, H; Dewenter, T A; Jetly, R
Abstract: Introduction/Objective: Monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) is an extranodal lymphoma arising from intestinal intraepithelial T-lymphocytes. Diagnosis is challenging obscured by non-specific gastrointestinal (GI) symptoms and radiographic findings, with potential delay in implementing therapy, as was encountered in a 40- year-old man of African-American descent with cachexia. Methods/Case Report: The patient presented with a two month history of nausea, vomiting, diarrhea and 10-15 pounds weight loss. Computed tomography revealed wall thickening of multiple large- and small-bowel loops. The clinical differential diagnoses included infectious enteritis and inflammatory bowel disease. Since symptoms improved during the hospital stay, he was discharged with future outpatient endoscopy planned but returned a month later with abdominal swelling and pain. On repeat imaging, he had ascites and small-bowel mechanical obstruction versus ileus. Straw-colored ascites, dilated friable segments of small-bowel, matted mesenteric lymph nodes, and adhesions were found on exploratory laparotomy. Small-bowel segments and appendix were resected. A prolonged hospital course ensued post-operatively with death due to multiple complications. Results (if a Case Study enter NA): The intestinal wall was grossly thickened with no discrete masses and microscopically had extensive infiltrates of small- to intermediate-sized, mature, minimally pleomorphic, CD3+/CD4- /CD5-/CD7+/CD8+/CD10-/CD20-/CD30-/CD56+/EBER-ISH- T-lymphocytes, focally infiltrating into the epithelium. Ascitic fluid cytology had small lymphocytes, CD2+/CD3+/CD4-/CD5-/CD10-/CD7+/CD8+/CD25-/CD30-/CD56+ /TCRαβ+/TCRγδ- by flow cytometry immunophenotyping. A diagnosis of MEITL was rendered based on these findings. Conclusion: MEITL is rare, aggressive, unassociated with celiac disease and usually seen in Asian and Hispanic populations. It presents with non-specific GI symptoms of abdominal pain, perforation, diarrhea, weight loss and intestinal obstruction underscoring the need for a high index of suspicion. Upper GI endoscopy has a limited role since involvement of small-bowel, specifically jejunum, is common. The evolving capsule endoscopy techniques may help in an early diagnosis. Due to limited literature, optimal treatment is unclear and various strategies using chemotherapy, surgery and stem-cell transplant have been tried with variable outcomes.